2020
DOI: 10.1128/mbio.01191-20
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Evolution in High-Osmolarity Environments

Abstract: Bacteria must maintain a cytosolic osmolarity higher than that of their environment in order to take up water. High-osmolarity environments therefore present formidable stress to bacteria. To explore the evolutionary mechanisms by which bacteria adapt to high-osmolarity environments, we selected Escherichia coli in media with a variety of osmolytes and concentrations for 250 generations. Adaptation was osmolyte dependent, with sorbitol stress generally resulting in increased fitness under conditions with highe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
(73 reference statements)
0
16
0
Order By: Relevance
“…to cope with the dynamic physicochemical conditions of the human large intestine. On one hand as a potential contributor to osmoregulation to survive osmotic shifts resulting from water absorption and transport of ions by colonic epithelial cells ( Costongs et al, 1985 ; Cesar et al, 2020 ); on the other hand to cope with the dynamic pH across the large intestine. On average, the pH of the human adult colon ranges from 5.7 (proximal) to 6.7 (distal; Fallingborg, 1999 ), but varies among individuals with values as low as 5.0 reported in healthy subjects ( Koziolek et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…to cope with the dynamic physicochemical conditions of the human large intestine. On one hand as a potential contributor to osmoregulation to survive osmotic shifts resulting from water absorption and transport of ions by colonic epithelial cells ( Costongs et al, 1985 ; Cesar et al, 2020 ); on the other hand to cope with the dynamic pH across the large intestine. On average, the pH of the human adult colon ranges from 5.7 (proximal) to 6.7 (distal; Fallingborg, 1999 ), but varies among individuals with values as low as 5.0 reported in healthy subjects ( Koziolek et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our CR model and fitting procedure can also be used to aid the parametrization of other models such as Lotka-Volterra models ( Figure 4—figure supplements 1 – 5 ), comparisons among which can reveal the model details that are required to recapitulate experimental data. In the future, more detailed hypotheses can be generated by investigating how time series statistics are affected by modifications to baseline CR dynamics, such as the incorporation of metabolic cross-feeding ( Goldford et al, 2018 ; Li et al, 2020 ) or physical interactions such as type VI killing ( Verster et al, 2017 ), functional differentiation from genomic analysis ( Arkin et al, 2018 ; Machado et al, 2021 ; Pollak et al, 2021 ), and physical variables such as pH ( Aranda-Díaz et al, 2020 ; Ratzke and Gore, 2018 ), temperature ( Lax et al, 2020 ), and osmolality ( Cesar et al, 2020 ). In addition, recent studies have shown that evolution can substantially affect the dynamics of human gut microbiotas ( Garud et al, 2019 ; Yaffe and Relman, 2020 ; Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown earlier that under non-stress conditions, bacteria favor phytohormone synthesis rather than osmolyte accumulation, whereas the opposite occurs under stress conditions. Such a shift in metabolic activity is common in bacterial cells, allowing them to maintain homeostasis when there is an increase in osmotic pressure in the extracellular medium ( Varela et al, 2004 ; Lahtvee et al, 2014 ; Cesar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%